Short Communication: Morphological characteristics and morphometric of Stingless Bee (Apidae: Hymenoptera) from Banten Province, Indonesia - ADE EFIN; TRI ATMOWIDI; TARUNI SRI PRAWASTI (Society for Indonesian Biodiversity, 2019)
Abstract. Efin A, Atmowidi T, Prawasti TS. 2019. Short Communication:  Morphological Characteristics and Morphometric of Stingless Bee (Apidae:  Hymenoptera) from Banten Province, Indonesia. Biodiversitas 20:  1693-1698. Tetragonula (Meliponini:  Apidae) belong to stingless bees that characterized by complex communication, permanent colonies with division of castes, i.e., queen, males, and workers. This paper described morphological characters and morphometric study of stingless bee from Pandeglang, Banten Province, Indonesia. Local people (Sundanese) known as the specimen examined is “teuweul omas” that have different in nest entrance characteristics compare to nest of Tetragonula laeviceps found commonly. In average, specimens examined were 4.445±0.072 mm body length, 1.911±0.019 mm head width, mesoscutum has distinct hair bands separated by glabrous interspaces area, with plumose frontal hairs, and black metasoma, legs, and hairs on the frontal. Male genitalia of stingless bee examined are long gonostylus and slender with sparse hairs at apex, penis valve is very robust, tapering at the apex and shorter than gonostylus. Based on morphological characteristics and morphometric measurements, we identified the specimen examined is Tetragonula cf. laeviceps.